2003
DOI: 10.1126/science.1085116
|View full text |Cite
|
Sign up to set email alerts
|

Thermohaline Fine Structure in an Oceanographic Front from Seismic Reflection Profiling

Abstract: We present acoustic images of oceanic thermohaline structure created from marine seismic reflection profiles across the major oceanographic front between the Labrador Current and the North Atlantic Current. The images show that distinct water masses can be mapped, and their internal structure imaged, using low-frequency acoustic reflections from sound speed contrasts at interfaces across which temperature changes. The warm/cold front is characterized by east-dipping reflections generated by thermohaline intrus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
220
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(229 citation statements)
references
References 16 publications
3
220
0
5
Order By: Relevance
“…Temperature-salinity contrasts in the water column result in small changes in sound speed and appear in seismic images as distinct reflection layers revealing exceptional detail between 10-100 m horizontal resolution throughout the water column. Spectacular images of thermohaline finestructure in the ocean include features such as intrusions (Holbrook et al, 2003), fronts (Holbrook et al, 2003;Nakamura et al, 2006), water mass boundaries (Nandi et al, 2004), internal waves (Holbrook and Fer, 2005;Krahmann et al, 2008), internal tide characteristics ) and mesoscale eddies (Biescas et al, 2008;Pinheiro et al, 2010). A clear relationship has been established between recorded seismic reflectance and the presence of thermohaline finestructure (Nandi et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Temperature-salinity contrasts in the water column result in small changes in sound speed and appear in seismic images as distinct reflection layers revealing exceptional detail between 10-100 m horizontal resolution throughout the water column. Spectacular images of thermohaline finestructure in the ocean include features such as intrusions (Holbrook et al, 2003), fronts (Holbrook et al, 2003;Nakamura et al, 2006), water mass boundaries (Nandi et al, 2004), internal waves (Holbrook and Fer, 2005;Krahmann et al, 2008), internal tide characteristics ) and mesoscale eddies (Biescas et al, 2008;Pinheiro et al, 2010). A clear relationship has been established between recorded seismic reflectance and the presence of thermohaline finestructure (Nandi et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Holbrook et al (2003) first related water-column reflections to oceanic finestructure in a front between the Labrador Current and the North Atlantic Current. A descriptive introduction on the seismic reflection method with a focus on water column interpretations can be found in Fer and Holbrook (2008), Ruddick et al (2009), andPinheiro et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…This work illustrates the great potential of multichannel finestructure of meddies with exceptional vertical resolution 10 m and horizontal resolution 100 m [8]. Several studies of seismic oceanoprahy have demonstrated the ability of seismic imaging to detect and map major features in the ocean, including thermohaline finestructure and water mass front [9], internal waves [5], currents [10], eddies in Cadiz Bay [10], and boundary mixing [6]. In Indonesia, this study was conducted by Wirda (2016) in detecting structure of water column in East Waigeo, Papua.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1980s, Gonella & Michon [7] and Phillips & Dean [8] found that the oceanic fine structure could be mapped by analysis of a seismic data set; however, their work received little attention. In the beginning of this century, Holbrook et al [9] discovered from three seismic sections near the Gorringe Ridge that imaged reflectors correspond to oceanic thermal structures, and that the characteristics of seismic reflections vary with different water masses. Subsequently, several studies in seismic oceanography have shown that the interface between the upper warm current and lower cold water in the Norwegian Sea can produce strong reflections [10]; that the amplitude of reflections from the boundary between the warm Kuroshio current and the cold Oyashio water changes markedly [11]; and that the reflectors in the upper and lower parts of mesoscale eddies are complicated [12].…”
mentioning
confidence: 99%